Responses of the arbuscular mycorrhizal fungi community to warming coupled with increased drought in an arid desert region - Ting Xie; Yuwei Lin; Xinrong Li (Geoderma, 2024)
Warming coupled with precipitation changes induced by climate change profoundly affect desert ecosystem functions in global drylands. Arbuscular mycorrhizal fungi (AMF) play a crucial role in such ecosystems by regulating energy and nutrient exchange. However, little is known about how AMF communities respond to warming coupled with reduced precipitation (W + RP). We evaluated the impacts of 0.5 °C and 1.5 °C increase in temperature coupled with 5 % and 8 % reductions in total annual precipitation (0.5 °C W + 5 % RP, 1.5 °C W + 8 % RP) on AMF communities and the main ecological processes structuring AMF community assemblies in the rhizosphere soil of typical winter annual plants in the Tengger Desert, northwest China. The results showed that warming coupled with reduced precipitation could significantly alter the composition, abundance, and diversity of AMF communities. Both AMF biomass and AMF diversity increased in the 0.5 °C W + 5 % RP treatment but decreased in the 1.5 °C W + 8 % RP treatment. The 1.5 °C W + 8 % RP treatment significantly reduced root biomass and the AMF colonization rate but increased the specific root length, indicating a trade-off between fine roots and their symbiotic AMF. The AMF community was phylogenetically random in the 0.5 °C W + 5 % RP treatment but appeared clustered in the 1.5 °C W + 8 % RP treatment, implying that more pronounced warming coupled with reduced precipitation can promote the deterministic assembly of the AMF community. We provide a conceptual framework for comprehending the mechanisms underlying the effects of warming coupled with reduced precipitation on AMF communities, incorporating biological and geochemical processes. Overall, the findings of this study suggest that AMF abundance and diversity and the main ecological processes driving AMF assemblages respond differently to more pronounced compared to less intensive warming coupled with reduced precipitation. Importantly, higher warming coupled with a reduction in precipitation reduced plant dependence on AMF and resulted in stronger environmental filtration by significantly reducing soil water content.